Automated image analysis of placental villi and syncytial knots in histological sections. (May 2017) - Kidron, Debora; Vainer, Ifat; Fisher, Yael; Sharony, Reuven
Abstract: Introduction: Delayed villous maturation and accelerated villous maturation diagnosed in histologic sections are morphologic manifestations of pathophysiological conditions. The inter-observer agreement among pathologists in assessing these conditions is moderate at best. We investigated whether automated image analysis of placental villi and syncytial knots could improve standardization in diagnosing these conditions. Methods: Placentas of antepartum fetal death at or near term were diagnosed as normal, delayed or accelerated villous maturation. Histologic sections of 5 cases per group were photographed at ×10 magnification. Automated image analysis of villi and syncytial knots was performed, using ImageJ public domain software. Analysis of hundreds of histologic images was carried out within minutes on a personal computer, using macro commands. Results: Compared to normal placentas, villi from delayed maturation were larger and fewer, with fewer and smaller syncytial knots. Villi from accelerated maturation were smaller. The data were further analyzed according to horizontal placental zones and groups of villous size. Discussion: Normal placentas can be discriminated from placentas of delayed or accelerated villous maturation using automated image analysis. Automated image analysis of villi and syncytial knots is not equivalent to interpretation by the human eye. Each method has advantages and disadvantages in assessing the 2-dimensional histologic sections representing the complex, 3-dimensional villous tree. Image analysis of placentas provides quantitative data that might help in standardizing and grading of placentas for diagnostic and research purposes. Highlights: Diagnosing delayed or accelerated maturation of placental villi in histologic sections is subjective. Automated image analysis of villi and syncytial knots can discriminate normal from abnormal villi. Automated image analysis of villi is supplementary and not equivalent to human eye interpretation. It can increase accuracy, standardization and inter-observer agreement. It may also facilitate grading placentas for diagnostic and research purposes.